2021
DOI: 10.3389/fpsyg.2021.634863
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Responses to Covid-19 Pandemic: Religions, Illness Perception, and Perceived Stress

Abstract: Many psychological researchers have proven the deteriorating effects of the coronavirus disease 2019 (Covid-19) pandemic on public mental health. In Malaysia, various Covid-19 clusters were associated with religious gatherings. From a cultural psychology perspective, how ethno-religious groups respond to this crisis originating from their unique rationality and ecological systems. Therefore, this study aimed to explore the illness perceptions of major religious groups (Christian, Muslim, and Buddhist) in Malay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 80 publications
4
33
0
3
Order By: Relevance
“…Mills and colleagues describe the Thai culturally embedded coping strategy of acceptance ('Thum-jai') as "accepting and letting go of the negative situation, forgetting the bad feeling, calming or steadying the mind, and developing patience and understanding" [86], finding that the emotion-based coping strategy of 'Thum-jai' helped Thai people develop purposeful approaches of thinking and acting in light of adverse events which cannot be changed [87]. Our findings also echo other research on the positive association between social support and coping from Thailand (e.g., HIV [88], breast cancer [89,90] and COVID-19 [91]) and internationally (e.g., religious coping in the context of COVID-19 [92][93][94][95], healthy ageing [96] and terminal illness [97]), highlighting the important and beneficial role of spirituality and religion in coping with adverse health events and crises. Similarly, a qualitative study examining mental health impacts and coping strategies among disadvantaged groups in India during COVID-19 lockdown found that religion and devotional practices played an important role in participants coping strategies, by helping them make sense and find meaning in the COVID-19 crisis.…”
Section: Copingsupporting
confidence: 84%
“…Mills and colleagues describe the Thai culturally embedded coping strategy of acceptance ('Thum-jai') as "accepting and letting go of the negative situation, forgetting the bad feeling, calming or steadying the mind, and developing patience and understanding" [86], finding that the emotion-based coping strategy of 'Thum-jai' helped Thai people develop purposeful approaches of thinking and acting in light of adverse events which cannot be changed [87]. Our findings also echo other research on the positive association between social support and coping from Thailand (e.g., HIV [88], breast cancer [89,90] and COVID-19 [91]) and internationally (e.g., religious coping in the context of COVID-19 [92][93][94][95], healthy ageing [96] and terminal illness [97]), highlighting the important and beneficial role of spirituality and religion in coping with adverse health events and crises. Similarly, a qualitative study examining mental health impacts and coping strategies among disadvantaged groups in India during COVID-19 lockdown found that religion and devotional practices played an important role in participants coping strategies, by helping them make sense and find meaning in the COVID-19 crisis.…”
Section: Copingsupporting
confidence: 84%
“…Malay Muslims believed suffering and diseases were trials from God for a better life in the everlasting world, while Chinese Taoists perceived illnesses to be an imbalance of forces in the body system. On the contrary, Christians may believe illnesses are due to personal sins and are a form of cleansing ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it was reported that the mental disorders are perceived as an opportunity to remedy disconnection from God, which might be considered as positive since it reinforces the Muslim attitudes toward mental illness. Hence, a recent study on the religion commitment showed that reduced depressive and stress, better health, and subjective well-being may be seen in people with higher intrinsic religiosity and spirituality ( Ting et al, 2021 ). Accordingly, mental well-being is a crucial aspect that must be addressed during this pandemic as all means of communication revolve around the coronavirus.…”
Section: Introductionmentioning
confidence: 99%